THE APPLICATION OF ISLAMIC LAW IN INDONESIA: BETWEEN OPPORTUNITIES AND CHALLENGES - Hejazziey, Djawahir (Center for Research and Development of Religious Literature and Heritage, 2015)
Essentially, the application of Islamic law in Indonesia has a huge opportunity. Undeniably, there remain challenges, both from within (Muslims) and from outside (other than Muslims). The great and tremendous challenges come from Muslims themselves. Muslims do not want Islamic law in Indonesia upright. The reason is the government is also unwilling because of the existing legal system and dissimilarity of attitude, understanding, practice of Muslims and Islamic leaders of Al-Quran and Al-Hadith, especially in relation to politics. It is likely to continue in line with the dynamics of Muslims in the state and nation. Pros and cons of Muslims against the application of Islamic law, including the unwillingness of groups against Islamic approach to structural (power) and Islamic cultural (culture), will raise the difficult and impossible application of Islamic law in Indonesia. Therefore, for most Muslims, the teachings should be reinterpreted beyond the textual meaning and application in real life.